Neurological outcomes of extended thymectomy for thymomatous myasthenia gravis: Subxiphoid vs. trans-sternal approaches - Zhu, Haoshuai; Liu, Zhihao; Yao, Xiaojing; Zou, Jianyong; Zeng, Bo; Zhang, Xin; Chen, Zhenguang; Su, Chunhua (Frontiers in Surgery, 2022)
Background The subxiphoid approach has been widely used recently. However, there is little data focusing on neurological outcomes in patients with thymomatous myasthenia gravis (MG) who underwent subxiphoid thoracoscopic thymectomy. The purpose of this study was to compare the neurological outcomes of patients with thymomatous MG who underwent extended thymectomy with a subxiphoid or transthoracic approach 1 year postoperatively. Methods The records of patients with Masaoka stage I and II thymomas who underwent extended thymectomy from January 2019 to December 2020 with tumor size less than 5 cm and thymomatous MG were retrospectively reviewed and evaluated. Neurological outcomes were measured by a quantitative myasthenia gravis score (QMGS), with a 2.3-point reduction in QMGS associated with improvement in clinical MG status. The clinical efficacy and variables affecting the outcomes were assessed using the Kaplan–Meier method and Cox proportional hazard regression analysis. Results A total of 89 patients were included in the analysis, of which 44 had a subxiphoid approach and 45 had a trans-sternal approach. Mean QMGS decreased from 12 at initial diagnosis to 8.7 preoperatively and 5.6 at 12 months postoperatively in the subxiphoid group and from 12.1 to 8.9 to 6.0 in the transthoracic group. Thirteen patients (28.9%) who underwent the trans-sternal approach and 10 (22.7%) who underwent the subxiphoid approach did not have an improved clinical status compared with their preoperative status. The median time to clinical improvement was 3 months (95% CI, 2.15–3.85) for the subxiphoid approach and 6 months (95% CI, 5.54–6.46) for the trans-sternal approach. Univariate results showed that the subxiphoid approach was associated with a faster improvement in clinical status (HR = 1.701, 95% CI, 1.044–2.773, P < 0.05), and age ≦48 was associated with a faster improvement in clinical status (HR = 1.709, 95% CI, 1.044–2.799, P < 0.05). The multivariate model including age ≦48 (HR = 1.837, 95% CI, 1.093–3.086, P = 0.022) and the subxiphoid approach (HR = 1.892, 95% CI, 1.127–3.177, P = 0.016) was significantly associated with a faster improvement in clinical status. Conclusions In patients with Masaoka stage I and II thymoma who underwent thymectomy, with tumor size less than 5 cm and thymomatous MG, age ≦48 years and the subxiphoid approach were associated with a rapid improvement in clinical status.